Species profiles life histories and environmental requirements of coastal fishes and invertebrates (North Atlantic)--American shad - Weiss-Glanz, Lori S.; Stanley, Jon G.; Moring, John R. (Washington, D.C. U.S. Department of the Interior, 1986)
U.S. Fish Wildl. Serv. Biol. Rep. 82(11.59)
Keywords: Invertebrates; Fishes; History; American shad--North Atlantic